PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI DISIPLIN KERJA PADA PT. PELINDO JASA MARITIM - Rachmawati; Latief, Fitriani; Mariah, Mariah (Jurnal Bisnis dan Kewirausahaan, 2024)
This study aims to determine the effect of work motivation and organizational climate on employee performance through work discipline at PT Pelindo Jasa Maritim. The research sample size was taken using the Slovin formula with an error tolerance of 10%, so that 88 respondents were obtained who were employees of PT Pelindo Jasa Maritim. The study used a path analysis method with data collection using a questionnaire with a Likert scale. The results showed that, 1) Work Motivation has a positive and significant influence on Employee Performance; 2) Organizational Climate has a positive and significant influence on Employee Performance; 3) Work Motivation has a positive and significant influence on Work Discipline; 4) Organizational Climate has a positive and significant influence on Work Discipline; 5) Work Discipline has no significant influence on Employee Performance; 6) Work Discipline cannot mediate the relationship between Work Motivation and Employee Performance; and 7) Work Discipline cannot mediate the relationship between Organizational Climate and Employee Performance.